Effect of Water on CO2 Adsorption on CaNaY Zeolite: Formation of Ca2+(H2O)(CO2), Ca2+(H2O)(CO2)2 and Ca2+(H2O)2(CO2) Complexes - Nikola L. Drenchev; Boris L. Shivachev; Lubomir D. Dimitrov; Konstantin I. Hadjiivanov (Nanomaterials, 2023)
Efficient CO2 capture materials must possess a high adsorption capacity, suitable CO2 adsorption enthalpy and resistance to water vapor. We have recently reported that Ca2+ cations exchanged in FAU zeolite can attach up to three CO2 molecules. Here we report the effect of water on the adsorption of CO2. Formation of Ca2+(H2O)(CO2), Ca2+(H2O)(CO2)2 and Ca2+(H2O)2(CO2) mixed ligand complexes were established. The Ca2+(H2O)(CO2) species are readily formed even at ambient temperature and are characterized by ν(12CO2) and ν(13CO2) infrared bands at 2358 and 2293 cm−1, respectively. The Ca2+(H2O)(CO2)2 species are produced at low temperature and are identified by a ν(13CO2) band at 2291 cm−1. In the presence of large amounts of water, Ca2+(H2O)2(CO2) complexes were also evidenced by ν(12CO2) and ν(13CO2) bands at 2348 and 2283 cm−1, respectively. The results demonstrate that, although it has a negative effect on CO2 adsorption uptake, water in moderate amounts does not block CO2 adsorption sites.